PsycEXTRA Dataset 1969
DOI: 10.1037/e435522004-001
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition, retention, and retraining: Effects of high and low fidelity in training devices.

Abstract: This study is the first in a series which was conducted under the name STRANGER III, and which was to examine trainee's long-term memory of motor skills. This phase examined the effects of varying fidelity of training devices on acquisition, retention, and reinstatement of ability to perform a 92-step procedural task. Three versions of the Section Control Indicator Cc. nsole of the Nike-Hercules guided missile system were utilized. One version was a physical duplicate, fully powered and operational; a second h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1973
1973
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…All-hough data are lacking with respect to the maintenance of Army job-relevant procedures, data on the maintenance of basic combat training skills (83,141), the preparation and firing of a Nike-Hercules missile (54,55), and gunnery proficiency in a combat air force (World War II) (114) support the contention that procedural proficiency cannot be maintained in the absence of regular practice.…”
Section: -)mentioning
confidence: 99%
See 2 more Smart Citations
“…All-hough data are lacking with respect to the maintenance of Army job-relevant procedures, data on the maintenance of basic combat training skills (83,141), the preparation and firing of a Nike-Hercules missile (54,55), and gunnery proficiency in a combat air force (World War II) (114) support the contention that procedural proficiency cannot be maintained in the absence of regular practice.…”
Section: -)mentioning
confidence: 99%
“…For illustration, the acquisition and longterm retention of a 92-step proceduial task (firing a Nike-Hercules missile) following training on a high-functional similarity drawing of the operational equipment has been shown to equal learning and retention following training on the actual equipment (54,55).…”
Section: Training Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A numLer of studies have shown that low-cost devices, such as mock-ups, charts, and flat panel simulators are as effective as real equipment for training personnel to operate (rather than maintain) equipment (Grimsley 1969;Denenberg 1954;Torkelson 1954;Swanson 1954;Vris 1955;Spangenberg 1974;French and Martin 1957;Prophet and3oyd 1970, Dougherty, Houston, andNicklas 1957;and Cox, Wood, Boren et al, 1965. Useful reviews of this topic may be found in Micheli 1972, Kinkade and Wheaton 1972, and Fink and Shriver 1978.…”
Section: Fidelity Of Simulationmentioning
confidence: 99%
“…Usually, organizations plan specific adapting training to facilitate the transfer process [46]. Simulators with limited physical fidelity are often quite adequate [39,47]. For example, there is little evidence that motion in flight simulators, which cannot approach the actual motion of an aircraft, offers positive transfer benefits [48].…”
Section: Slow Beginningmentioning
confidence: 99%